KARUNGUT FOR THE DAYAK COMMUNITY OF CENTRAL KALIMANTAN AS A MEANS OF PRESERVING REGIONAL ARTS - Ropikha Lidia Silap; Gea Octavilla, Nia Olivia, Jesica Agnesia Keren, Maria Veronica, Natanael Yehezkiel Mamarimbing, And (Adisam Publisher, 2024)
Karungut is a traditional art originating from the Dayak culture of Central Kalimantan in the form of songs or chants such as rhymes or poems that contain morals or messages of encouragement to build the Ngaju Dayak community. The types of Karungut in Central Kalimantan are Karungut Deder, Karungut Traditional, Karungut Modem. This research is a qualitative research with data collection through literature review. The literature review contained in it includes: previous research and analysis of Karungut. The purpose of Karungut is used in welcoming ceremonies, traditional events and weddings or in regional art performances. Karungut is one of the cultures in Central Kalimantan that has existed for a long time and is still preserved by the Dayak people. The Karungut singers create lyrics that tell about the outpouring of the heart, love, advice, to the story of one's life. Currently, Indonesian society faces challenges related to the value of Pancasila in the life of the nation and state, from this art culture can be used as a tool to grow Pancasila values in the lives of people, especially the Dayak people in Central Kalimantan.